Regulation of Evidence in the Criminal Procedure Code: A Comparison to the Draft Law on Criminal Procedure - Maharani, Sandrina Darma; Wulandari, Ni Gusti Agung Ayu Mas Tri (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
This article examines the regulation of evidence in the Indonesian Criminal Procedure Code (KUHAP) and compares it with the provisions in the Draft Criminal Procedure Code (RUU KUHAP), in light of the evolving demands for reform in criminal procedural law. The purpose of this study is to analyze the current evidentiary rules in KUHAP and evaluate the relevance and effectiveness of the proposed changes in the RUU KUHAP as part of broader procedural reform efforts. This research adopts a normative legal method, employing a statutory and comparative approach by examining the normative content of both KUHAP and RUU KUHAP and comparing them with evidentiary concepts in other legal systems. The findings indicate that the RUU KUHAP introduces a more modern approach to evidence, including the recognition of electronic evidence and the strengthening of suspects’ rights. These findings contribute to the discourse on criminal procedure reform and highlight the need to adapt procedural law to technological developments and human rights standards.